Effect of Ethanol Extracts of Mustard Green (Brassica rapa L.) on Streptozotocin Induced Rats - Sri Wahjuni (Journal of Global Pharma Technology, 2020)
Objective: This experimental study was conducted to evaluate the effect of the mustard green extract on blood glucose and the pancreas histopathological feature. Methods: Five groups of rats divided into the control group that received standard food (P0) and streptozotocin-induced group (P1, P2, P4, and P4). P1 (positive control group) was given glibenclamide; P2, P3, and P4 (treatment group) were given mustard green ethanol extract at a dose of 0.5; 2.0; and 5.0 mg/kg body weight/day respectively. The separation of ethanol extract of mustard green was carried out by LC-MS/MS. One way ANOVA and Post hoc test was conducted to evaluate the mean difference of the blood glucose. Results: Post hoc test showed significant result for P0 vs P3 (p<0.001), P0 vs P4 (p=0.001), P1 vs P2 (p=0.048), P2 vs P3 (p=0.001). Comparison between P1 and treatment group was found a similar effect on blood glucose between P1 vs P3 (p=0.048) and P1 vs P4 (p=0.830). Histological studies showed the administration of ethanol extract of mustard green showed a restorative effect. Conclusion: Administration of ethanol extract of mustard green decrease the level of blood glucose and might be a usable treatment for hyperglycemia.Keywords: Mustard green (Brassica rapa L.), Streptozotocin, Hyperglycemic effects.